Pengembangan Tes Uraian Untuk Identifikasi Profil Keterampilan Berpikir Kritis Materi Ikatan Kimia Siswa Kelas XI SMAN 7 Mataram - Nur Ismiyahyi; I Nyoman Loka; Muti’ah Muti’ah (Chemistry Education Practice, 2025)
This research is a type of Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate) which aims to develop a description test instrumen to identify critical thinking skills of class XI students of SMAN 7 Mataram on chemical bonding material. The instrumen was developed by fulfilling the criteria of validity, reliability, level of difficulty, and distinguishing power. Validation was carried out by three experts, consisting of two Chemistry Education lecturers at Mataram University and one chemistry teacher at SMAN 7 Mataram. The results of content validity using Aiken's V with an average value of 0.82 which is classified as having a very high level of validity. Empirical validity states that all seven items are valid with the highest value reaching 0.83. The reliability test rcount of 0.813 is greater than the rtable indicates the item is reliable. The level of difficulty of the questions is in the medium category which ranges from 0.52-0.66. Differentiating power is in the sufficient to very good category ranging from 0.26-0.72. Students' critical thinking skills assessed using the developed instrumen were sufficient with an average value of 58.